Epitaxy, structure, phase and magnetic state of the films, synthesized in Ni laser plasma - A. G. Bagmut; I. G. Shipkova; V. A. Zhuchkov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2009)
The structure, phase state and changing of density and magnetic properties where studied at recrystallization of thin films of laser condensates of nickel. For two cases of epitaxial growth with HCP crystal lattice (phase α-Ni) and with BCC crystal lattice (phase β-Ni) orientation relations “film–substrate” (001) KCl where established. An orientation relation between phases of α-Ni and of β-Ni, that takes place during polymorphous transformation at the film annealing, was determined. It was demonstrated, that as the result of a polymorphous transformation there is a change of magnetic characteristics. Density increases, (at 18.5 %); films get magnetic properties and hysteresis takes place at magnetization reversal.